Effect of concentration and relative position of wood and coal particles on the characteristics of the mixture ignition process. (15th August 2020) - Kuznetsov, G.V.; Syrodoy, S.V.; Kostoreva, A.A.; Kostoreva, Zh.A.; Nigay, N.A.
Highlights: The results of experiments on the ignition of coal/wood fuel particles are presented. It is shown that biomass significantly accelerates the ignition of coal. We have established optimal (in terms of ignition dynamics) biomass concentration values in the fuel mixture. The optimum distance (for ignition) between the fuel particles has been established. Abstract: This article presents the results of experimental studies of the ignition of composite wood/coal fuel particles under high-temperature heating, corresponding to the internal furnace space of boiler units of thermal power plants. The ignition of a wood-coal mixture was studied based on coal and wood waste widely used in energy. For the first time in world practice, the basic regularities of the joint ignition of a group of wood and coal particles located at a certain distance from one another have been experimentally established. The ignition delay times (tign ) of each fuel particle in the group are determined. The influence of the concentration of wood and the relative position of the fuel particles relative to each other on the characteristics and conditions of ignition is analyzed. It was shown that in the temperature range Tg  = 873–1273 K, the gaseous products of wood pyrolysis begin to burn first, the coal particles burn second. In this case, the time interval between the ignition of wood and coal does not exceed 1 s, with a distance between particles of up to 10 mm. According to the results of experiments, it was also found that the optimal component ratio in the wood/coal system lies in the range from 30/70 to 35/65. It is shown that at a high concentration of coal in the wood-coal mixture, coal particles act as a kind of screen that blocks thermal radiation from the external environment to the wood particles.